Mild Renal Dysfunction and Metabolites Tied to Low HDL Cholesterol Are Associated With Monocytosis and Atherosclerosis - Ganda, Anjali (2013)
BACKGROUND: The number of circulating blood monocytes impacts atherosclerotic lesion size, and in mouse models, elevated levels of high-density lipoprotein cholesterol suppress blood monocyte counts and atherosclerosis. We hypothesized that individuals with mild renal dysfunction at increased cardiovascular risk would have reduced high-density lipoprotein levels, high blood monocyte counts, and accelerated atherosclerosis. METHODS AND RESULTS: To test whether mild renal dysfunction is associated with an increase in a leukocyte subpopulation rich in monocytes that has a known association with future coronary events, we divided individuals from the Malmö Diet and Cancer study (MDC) into baseline cystatin C quintiles (n=4757). Lower levels of renal function were accompanied by higher monocyte counts, and monocytes were independently associated with carotid bulb intima-media thickness cross-sectionally (P=0.02). Cystatin C levels were positively and plasma high-density lipoprotein cholesterol levels negatively associated with monocyte counts at baseline, after adjustment for traditional risk factors. Several amino acid metabolites tied to low levels of high-density lipoprotein cholesterol and insulin resistance measured in a subset of individuals (n=752) by use of liquid chromatography–mass spectrometry were independently associated with a 22% to 34% increased risk of being in the top quartile of monocytes (P<0.05). CONCLUSIONS: A low high-density lipoprotein cholesterol, insulin resistance phenotype occurs in subjects with mild renal dysfunction and is associated with elevated monocytes and atherosclerosis. High blood monocyte counts may represent a previously unrecognized mechanism underlying the strong relationship between cystatin C and cardiovascular risk.